2015
DOI: 10.1117/1.jmm.14.1.014001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wafer noise on the detection of 20-nm defects using optical volumetric inspection

Abstract: Patterning imperfections in semiconductor device fabrication may either be noncritical [e.g., line edge roughness (LER)] or critical, such as defects that impact manufacturing yield. As the sizes of the pitches and linewidths decrease in lithography, detection of the optical scattering from killer defects may be obscured by the scattering from other variations, called wafer noise. Understanding and separating these optical signals are critical to reduce false positives and overlooked defects. The effects of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…As the Authors have reported both simulated 19,31 and experimental 32,33 image data from defective and nominal semiconductor patterns previously, the limited number of images informed the decision to assess these loss functions using labeled ML image data sets. First, results reported should be wholly reproducible which requires open access image sets.…”
Section: Data Sets and Neural Networkmentioning
confidence: 99%
“…As the Authors have reported both simulated 19,31 and experimental 32,33 image data from defective and nominal semiconductor patterns previously, the limited number of images informed the decision to assess these loss functions using labeled ML image data sets. First, results reported should be wholly reproducible which requires open access image sets.…”
Section: Data Sets and Neural Networkmentioning
confidence: 99%
“…The simulations were performed using a well-verified [28][29][30] in-house implementation of the finite-difference time-domain [31] (FDTD) method to model the electromagnetic field scattered from the patterned layout and its defects. The incident angle of the illumination is chosen to be normal to the substrate for clarity; prior simulation results indicate that the defect detection often varies when using oblique illumination [29,32]. The linear polarization basis within the simulation is defined with respect to the long axis of the nominal pattern.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…In addition to measurement noise, "wafer noise" due to process variations is included [38][39][40][41][42]. Line edge roughness (LER) is known to be present in every lithographically manufactured device, either reducing the signal or increasing the noise [43].…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Experimental methods for making full use of this light field have included angle-resolved imaging in a high-magnification platform [5,16-18] as well as the acquisition of focus-resolved images for defect metrology [16,19,20] and dimensional metrology [14,21]. …”
Section: Scatterfield Microscopymentioning
confidence: 99%